The Influence of Lifestyle and Financial Literacy on the Use of Fintech Payments Paylater Among Students of the Faculty of Economics, Prima Indonesia University in Medan: engaruh Gaya Hidup dan Literasi Keuangan Terhadap Penggunaan Fintech Pembayaran Paylater di Kalangan Mahasiswa Fakultas Ekonomi Universitas Prima Indonesia Medan - Rivaldo Rivaldo; Afrizal; Melissa Mangali; Earvin John Medina (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
The rising adoption of financial technology, especially payment options like "buy now, pay later," is becoming more common among young individuals, especially students. This trend is very much connected to people wanting to buy more and more things and how well they can handle their own money. This research seeks to investigate how lifestyle and knowledge of financial matters affect whether students at the Faculty of Economics, Prima Indonesia University, Medan use "buy now, pay later" services. In this study, a quantitative method was used, involving a sample group of 363 people, with the number decided by using the Slovin formula. The results indicated that lifestyle and understanding of finance have a large impact on whether people use "buy now, pay later" fintech services, both separately and as a whole. Both factors together accounted for 41.6% of the behavior related to using "buy now, pay later," with financial understanding being a bigger factor than lifestyle. These conclusions highlight how important it is to increase students' knowledge of finance, so they can use "buy now, pay later" services more carefully and in a way that lasts, without causing money problems later on.